P-47 Thunderbolt at war - Graff, Cory 1971- (The at war series, 2007)
Perhaps the most significant fighter aircraft of World War II, the Republic P-47 Thunderbolt was the largest and most powerful single-engine fighter of the war, and with over fifteen thousand P-47s built, its production numbers topped any other American fighter. P-47 Thunderbolt at War traces the history of the P-47, including the pioneering efforts of Alexander de Seversky and Alexander Kartveli, who designed the prototype; the features that played into the P-47s combat performance; and its wartime construction and testing.